DECISION-MAKING ASPECTS REGARDING DUAL CAREER FOR ATHLETES IN SOME EUROPEAN COUNTRIES - Onose Ionuț; Popescu Lucian; Moraru Cristina Elena; Radu Liliana Elisabeta; Onose Raluca Mihaela; Abalasei Beatrice Aurelia (Sport şi Societate)
The notion of a dual career for performance athletes implies, by definition, the involvement of related fields (work, education, health) in the field of sports. A country's rulers and those responsible for development policies must be aware ofthe vulnerability of athletes who end their careers.In reality, knowing the motivation, the desire for achievement in life by sports students, in relation to the different educational systems of Europe, can promote, according to Lupo et al. (2015), a better understanding of academic and sporting expectations, providing valuable information to decision makers in these areas. In this respect, cross-country comparisons, together with the determination of student athletes regarding dual careers, can contribute to the development of sustainable strategies for the realization of programs that combine education and sport.